EFFECTIVENESS OF VIDEO ASSISTED LEARNING MODULE - et al., K.PAAVIZHI (International Journal of Control and Automation, 2019)
Numerous educators and the teacher training institutions consider that the information resources as a best possibility for the modern teaching. Students in the current trend are bound to use the modern materials such as the video tutorials for learning purpose for almost anything say as from changing the vehicle tires till dancing. Significantly, the millennium has contributed to 92% of the videos online. Researches have proved that the usage of these short clip videos allows more efficiency in thinking and recall process. The visual and the audio combination in the videos have allowed for most of the users for the process of information in natural way. As an outcome, the educational institutions are facing the rising in demand for quality lectures in video formats and online courses that can be accessed inside the campus. Indeed, most of the students are creating self-videos on education.